A silyl porphyrin derivative conjugated with 6-deoxy-6-sulfo-α-d-glucopyranose functions as an efficient photosensitizer for photodynamic therapy - Hiroaki Horiuchi; Kota Nishikawa; Nozomi Ishii; Koki Kano; Shunsuke Shinada; Nene Osawa; Aoi Horikoshi; Toshitada Yoshihara; Fumio Sugawara; Kengo Sakaguchi; Tetsuo Okustu; Shinji Katsura; et al. (Photodiagnosis and Photodynamic Therapy)
We synthesized a new silyl porphyrin derivative conjugated with 6-deoxy-6-sulfo-α-d-glucopyranose (SGlc). Conjugation with SGlc improved A549 cellular uptake without significant changes in the photophysical and photochemical properties and subcellular localization. This improved cellular uptake led to enhanced photodynamic activity. Furthermore, conjugation with SGlc suppressed dark toxicity. These advantages were not observed for a conjugate with a glucose molecule. These results indicated that the conjugation with SGlc is a promising strategy for enhancing photodynamic efficacy.